Mastering the TPACK framework: Innovative approaches by mathematics teachers - Putri, Amelia Defrianti; Dadang Juandi; Al Jupri; Turmudi; Muchsin, Sitti Busyrah (Universitas Hamzanwadi, 2024)
Integrating technological, pedagogical, and mathematical content knowledge poses an inherent challenge. Educators are tasked with achieving a harmonious equilibrium among these facets to ensure the productive utilization of technology to bolster mathematical learning endeavors. This study examines how mathematics teachers in West Sumatra use Technology, Pedagogy, and Content Knowledge (TPACK) in their classrooms. The investigation engaged a cohort of 15 teachers and 36 students, employing a qualitative descriptive methodology. Methodologically, the research adopted a survey-based approach, with data collection techniques encompassing literature reviews, interviews, and questionnaires. This study’s findings underscored teachers’ adeptness in incorporating the TPACK framework throughout the various facets of the teaching process, encompassing planning, execution, and evaluation. Educators have adeptly woven TPACK principles into the fabric of mathematics instruction, meticulously integrating technological tools across all stages of the pedagogical journey. The judicious integration of technology has yielded palpable benefits, fostering a conducive and engaging learning environment for students. Moreover, the findings of this research serve as a clarion call for further scholarly inquiry aimed at enhancing the efficacy and quality of TPACK-infused digital learning practices.